SYSTEM AND METHOD FOR CLASSIFYING MICROSCOPIC PARTICLES - Austin Venelinov, Daniels (2024)
A system and method for classifying images of particles detected in a fluid. Particles images of a dataset are preprocessed through computer processing and analyze for classification with an Artificial Intelligence (AI) classifier to predict which of one or more pre-defined particle types are present in the particle images of the dataset. The AI classifier is trained with smart training data and a smart training method to enable enhanced recognition of variations between dataset particle images and one or more pre-defined particle types. Particle images are subject to extreme augmentation to facilitate robust classification performance. The invention includes detecting anomalies of the particle images of the dataset to detect images that are inconsistent with images known to be of the class the image is assigned during preliminary image classification. Fake particle images may be generated to improve the detection of anomalies of the particle images classified.